A conversation with Ray Ozzie. - O'Hanlon, Charlene (New York ACM, 2005)
Cooperate, communicate, collaborate
Keywords: Computing Milieux; History of Computing; People; General Literature; General; Biographies/Autobiographies.; Miscellaneous; The computing profession